Divine diagrams : the manuscripts and drawings of Paul Lautensack (1477/78-1558) - Kress, Berthold (Library of the written word, 2014)
After the Reformation the successful painter Paul Lautensack (1477/78-1558) dedicated himself to spreading revelations on the nature of God. Lautensack was besides Dürer the only German artist who wrote against the iconoclasts, and he believed that he as a painter could explain the images of Revelation better than theologians like Luther. He presented his insights in hundreds of highly sophisticated diagrams that display a wide range of material accessible to an urban craftsman, from the vernacular Bible to calendar illustrations. This study is the first monograph on this extraordinary man, it presents a corpus of his surviving works, analyzes his peculiar theology of the image and locates the elements of his diagrams in the visual world of the Reformation period.